HPV Vaccine Communication and Administration for the Prevention of Oropharyngeal Cancer in Dental Primary Care: Perspectives of Professionals and Students—A Systematic Review - Kenneth Sik-Kwan Chan; Tin-Shun Titan Mak; Ollie Yiru Yu; Victor Ho-Fun Lee; Chun-Hung Chu; Siu-Chee Sophia Chan; Horace Cheuk-Wai Choi (Vaccines)
Background/Objectives: The rising prevalence of HPV-associated oropharyngeal cancer (OPC) presents a significant concern, prompting dental professionals to play an increasingly vital role in HPV vaccination and prevention within primary healthcare. This study aimed to assess the current knowledge, attitudes, and practices of dental professionals and students regarding HPV, the HPV-OPC association, and HPV vaccine communication and administration in dental settings to pinpoint areas for improvement and develop targeted interventions. Methods: This study involved a literature search in PubMed/MEDLINE, Embase, and Scopus for research outputs published from 1 January 2006 to 31 December 2024. Eligible studies examined the knowledge, perceptions, and behaviors of dental professionals and students regarding HPV and HPV-OPC. The Risk of Bias Tool was used to evaluate the bias risk in all included studies Results: Forty-two studies with a low bias risk were analyzed. While general HPV knowledge was evident in both dental practitioners and students, deficiencies in understanding HPV-OPC and vaccination were identified. Only 9% of dental practitioners discussed HPV vaccination, but future students showed greater willingness (40–80%) to engage in these discussions. Among dental professionals, common barriers included discomfort and a lack of confidence in discussing HPV vaccination. Attitudes towards administering the HPV vaccine varied between dental practitioners and students, with an interest in training programs for readiness. Liability concerns were highlighted as a significant barrier for both groups, impacting their confidence in vaccine administration. Conclusions: The findings highlight the need for strategies and areas to enhance knowledge and confidence in discussing HPV vaccines in dental primary healthcare settings, offering valuable insights for researchers and policymakers to plan programs that enhance the readiness of dental professionals to administer HPV vaccines.